Further investigations on the PHAEOTHAMNIOPHYCEAE using a multigene phylogeny, with descriptions of five new species. Issue 2 (30th December 2019) - Graf, Louis; Yang, Eun Chan; Boo, Ga Hun; Andersen, Robert A.; Yoon, Hwan Su
Abstract : We examined 12 strains representing eight species classified in the algal class Phaeothamniophyceae (Heterokontophyta). Based upon a five‐gene molecular phylogeny (nuclear‐encoded SSU rRNA and plastid‐encoded psa A, psb A, psb C, and rbc L) and light microscopic observations, we describe five new species: Phaeoschizochlamys santosii sp. nov., Phaeoschizochlamys siveri sp. nov., Phaeothamnion wetherbeei sp. nov., Stichogloea dopii sp. nov. and Stichogloea fawleyi sp. nov. The Phaeothamniophyceae, as delimited here, form a natural group that is sister to the Aurearenophyceae. Molecular phylogenetic analyses proved more reliable than morphological characters for distinguishing species. Evolutionary trends with the SI clade of the heterokont algae are discussed.